Electron flow in organic chemistry : a decision-based guide to organic mechanisms - Scudder, Paul H. (Hoboken, New Jersey : Wiley, 2013)
"The revised 2nd edition builds on and improves this legacy, continuing the rigorous mechanistic approach to organic chemistry. Each mechanistic process is divided into its basic units, the dozen common electron flow pathways that become the building blocks of all the common mechanistic processes"--
Fakulti Sains Bumi.
Includes bibliographical references (pages 364-365) and index.
Keywords: Charge exchange; Chemical bonds; Chemistry, Organic